2020
DOI: 10.3389/fpsyg.2020.01067
|View full text |Cite
|
Sign up to set email alerts
|

Striving to Become a Better Teacher: Linking Teacher Emotions With Informal Teacher Learning Across the Teaching Career

Abstract: The importance of informal teacher learning (ITL) to teaching effectiveness and student achievement has been repeatedly demonstrated, but there is limited research into the personal antecedents of ITL. We analyzed the relationships between teacher emotions and participation in five different kinds of ITL activities (learning through media, colleague interaction, stakeholder interaction, student interaction, and individual reflection) among 2,880 primary teachers (85.49% female) with a large range of teaching e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 82 publications
0
21
0
2
Order By: Relevance
“…The frequency of college faculty engagement in online IL activities was measured using the Informal Learning Scale, which is developed and revised by the authors of this study, with reference to other Informal Learning Scales about primary and middle school teachers (Bakkenes et al, 2010 ; Huang et al, 2020 ). The scale contains seven items.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of college faculty engagement in online IL activities was measured using the Informal Learning Scale, which is developed and revised by the authors of this study, with reference to other Informal Learning Scales about primary and middle school teachers (Bakkenes et al, 2010 ; Huang et al, 2020 ). The scale contains seven items.…”
Section: Methodsmentioning
confidence: 99%
“…However, the two properties are well rooted in the literature. One is self-directed learning, with the learning content and form determined by learners themselves (Conlon, 2004 ; Marsick et al, 2017 ; Huang et al, 2020 ). The other is to learn through interaction and reflection, e.g., actively seeking feedback and debriefing work experiences (Manuti et al, 2015 ; Louws et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…IL often occurs as people carry out their work and acquire the necessary competence and interests to meet current and future work requirements (Jacobs and Park, 2009 ). IL mainly consists of four types: knowledge exchange, self-experimentation, environmental scanning and reflection (Lohman, 2005 ; Bakkenes et al, 2010 ; Choi and Jacobs, 2011 ; Huang et al, 2020 ). From this perspective, community-based online learning at home during the COVID-19 pandemic can be regarded as a typical form of IL because teachers opted in to open online learning resources and learning is in the hands of the teachers themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Previous data suggests that the educational process, mediated by online computer technologies, requires a specific teaching experience [6]. It has been shown that teachers who have such communicative qualities as benevolence, openness, neuroplasticity, stress resistance, and the presence of self-regulation and self-discipline skills are more successful in the implementation of online courses [8,9,25,26]. However, the uniqueness of the situation of the forced and widespread transition to distance learning during the period of the COVID-19 pandemic threat causes a lack of research in the psychological consequences, mechanisms of adaptation to the new format, and the factors that determine its success.…”
Section: Discussionmentioning
confidence: 99%